2017
DOI: 10.1007/s11010-017-3154-2
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin increases the effect of 5-fluorouracil-based chemotherapy in human colorectal adenocarcinoma cells in vitro

Abstract: Melatonin has antitumor activity via several mechanisms including its anti-proliferative and pro-apoptotic effects. Moreover, it has been proven that melatonin in combination with chemotherapeutic agents enhances chemotherapy-triggered apoptosis in several types of cancer. Therefore, this study was intended to evaluate whether melatonin is able to strengthen the anti-cancer potential of different chemotherapeutic drugs in human colorectal adenocarcinoma HT-29 cells. We found that treatment with 20 µM cisplatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 40 publications
1
36
1
Order By: Relevance
“…Its anticancer mechanisms include acceleration of tumor cell apoptosis, suppression of tumor cell proliferation, immunostimulation and synergistic activity with other treatments. Recent studies have demonstrated that melatonin notably decreases the risk of death and treatment resistance of multiple malignancies, particularly in breast cancer, colon cancer, melanoma, lung cancer and malignant glioblastoma (7)(8)(9)31,32). A clinical study by Lissoni et al has demonstrated that the regression rate in patients with non-small-cell lung cancer or gastrointestinal cancer receiving combination therapy with chemotherapeutic drugs and melatonin was significantly higher compared with that in the group of patients receiving chemotherapy alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its anticancer mechanisms include acceleration of tumor cell apoptosis, suppression of tumor cell proliferation, immunostimulation and synergistic activity with other treatments. Recent studies have demonstrated that melatonin notably decreases the risk of death and treatment resistance of multiple malignancies, particularly in breast cancer, colon cancer, melanoma, lung cancer and malignant glioblastoma (7)(8)(9)31,32). A clinical study by Lissoni et al has demonstrated that the regression rate in patients with non-small-cell lung cancer or gastrointestinal cancer receiving combination therapy with chemotherapeutic drugs and melatonin was significantly higher compared with that in the group of patients receiving chemotherapy alone.…”
Section: Discussionmentioning
confidence: 99%
“…Its biological roles include regulation of the circadian rhythm, as well as antioxidant, anti-aging and immunoregulatory actions. Various studies have reported that melatonin has significant antitumor activity against several types of cancers, such as breast, lung and colorectal cancer (7)(8)(9). Although the exact mechanism remains unknown, the anticancer effects of melatonin may be mediated by multiple pathways, including antagonism of growth factors, induction of tumor cell apoptosis, enhancement of immunity, adjustment of the psychological state, and synergy with other treatments (10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…The addition of melatonin (1 mM for 48 hours) enhanced the in vitro antiproliferative capacity of 5‐FU, as well as its potential for inhibiting the formation of colonies, migration, and invasion. A second published study has demonstrated the significant augmenting effect of melatonin (1 mM for 72 hours) on the cytotoxicity of 5‐FU in human HT‐29 cells . The coadministration of melatonin potentiated significantly the cytotoxicity of 5‐FU, jointly achieving rates of ROS production and apoptosis on HT‐29 cells greater than the drug given separately.…”
Section: Synergistic Actions Of Melatonin As Adjuvant Treatment In Crcmentioning
confidence: 97%
“…A second published study has demonstrated the significant augmenting effect of melatonin (1 mM for 72 hours) on the cytotoxicity of 5-FU in human HT-29 cells. 319 The coadministration of melatonin potentiated significantly the cytotoxicity of 5-FU, jointly achieving rates of ROS production and apoptosis on HT-29 cells greater than the drug given separately. Both reports provided compelling evidence of the synergistic interplay between melatonin and 5-FU in CRC.…”
Section: Synergistic Actions Of Melatonin As Adjuvant Treatment In Crcmentioning
confidence: 98%
“…The PI is a membrane-impermeable dye. Hence, the state of the cell determines the ability of PI staining to distinguish between viable and late apoptotic cells (Pariente et al, 2018). At the end of the HP treatment (72 h), treated or resting cells were incubated with 250 μL binding buffer containing 5 μl of V-FITC for 15 min at room temperature in dark and then they were washed twice with 1X PBS, and finally the cells were incubated with 250 μL binding buffer containing 10 μL of PI for 15 min at room temperature in dark.…”
Section: Annexin V-fitc (Av-fitc) and Propidium Iodide (Pi) Assays Bymentioning
confidence: 99%